Kerangka Normatif Pembentukan Peraturan Daerah yang Humanis: Kajian Nilai Kearifan Lokal Masyarakat Magelang - Marizal, Muhammad; Gunawan, Tri Agus; Rihardi, Satrio Ageng; Rofiq, Nur; Puspandari, Rr. Yunita; Hadji, Kuswan (Jurnal Hukum IUS QUIA IUSTUM, 2026)
The formation of regional regulations (Perda) often ignores the cultural dynamics of local communities, thus triggering regulatory conflicts, as occurred in the case of the KSPN Borobudur and the implementation of policies on agricultural sector in Magelang. This study aims to map the forms of local wisdom values ​​that characterize the social characteristics of Magelang society while constructing a normative framework in the formation of humanistic and responsive Perda. The method used is qualitative with a normative-empirical research type through a conceptual and sociological approach. Data collection was carried out by purposive sampling in three representative locations, namely Gelangan Village (military site), Payaman Village (Islamic boarding school), and Wonolelo Village (mountain agrarian site). The results indicate that Magelang society is divided into three cultural typologies with unique value characteristics: the values ​​of discipline and obedience in the military community; the values ​​of friendliness and religiosity in the Islamic boarding school community; and the values ​​of simplicity and natural-cultural preservation in the mountain agrarian community. These empirical values ​​have been successfully normatively transformed into principles for designing regional laws that are in line with Law No. 12 of 2011, such as the principles of inclusivity, proportionality, and ecological sustainability. This study concludes that the integration of the three-typology of local wisdom is the primary foundation for a progressive-humanist regional legislative model. This normative model constructs three main prerequisites: conceptual reconciliation of positive law with living law from the planning stage, institutionalisation of socio-religious values ​​as mandatory considerations in the Academic Draft, and strengthening the space for substantive public participation to produce responsive and conscientious regional regulations.